2023
DOI: 10.3390/vetsci10020079
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Complex Probiotic Supplementation Changed the Composition of Intestinal Short-Chain Fatty Acids and Improved the Average Daily Gain of Growing Pigs

Abstract: At present, probiotics are being extensively evaluated for their efficacy as an alternative to antibiotics, and their safety in livestock production. In this study, 128 (Duroc, Yorkshire and Landrace) pigs with an average initial body weight of 28.38 ± 0.25 kg were allocated to four dietary treatments in a randomized complete-block design. There were eight pens per treatment, with four pigs per pen (two barrows and two gilts). Dietary treatments included: (1) control diet; (2) control diet + 0.05% complex prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…Energy and dry matter are also parameters that may vary depending on the study. Here, again, results differ between already-published studies [ 65 , 66 ]. The results from our study suggest that little to no increase in digestibility was achieved from the probiotic action.…”
Section: Discussioncontrasting
confidence: 99%
“…Energy and dry matter are also parameters that may vary depending on the study. Here, again, results differ between already-published studies [ 65 , 66 ]. The results from our study suggest that little to no increase in digestibility was achieved from the probiotic action.…”
Section: Discussioncontrasting
confidence: 99%
“…Wang et al. ( 68 ) observed that B. licheniformis significantly increased the content of acetic acid and butyric acid contents in the feces of growing pigs. VFAs regulate macrophage production of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…compared with the antibiotics fed group. However, some other studies found that supplement of probiotics (Lactobacillus plantarum, Saccharomyces cerevisiae, Bacillus subtilis, Enterococcus Faecium, Lactobacillus acidophilus) could reduce the ammonia contents in pig manure [32][33][34][35]. Wang et al [35] found decreased fecal ammonia and hydrogen sulfide emissions in 0.1% or 0.2% probiotic supplemented growing pig diet.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…However, some other studies found that supplement of probiotics (Lactobacillus plantarum, Saccharomyces cerevisiae, Bacillus subtilis, Enterococcus Faecium, Lactobacillus acidophilus) could reduce the ammonia contents in pig manure [32][33][34][35]. Wang et al [35] found decreased fecal ammonia and hydrogen sulfide emissions in 0.1% or 0.2% probiotic supplemented growing pig diet. Kim et al [25] showed that hydrogen sulfide and ammonia emissions were decreased in Bacillus licheniformis and B. subtilis supplemented diet in growing pigs.…”
Section: A C C E P T E Dmentioning
confidence: 99%